Brand Community Ritual Events as a Tool of Custom Culture Reproduction and Marketing - LATIF, Nashrudin; SUHARIYANTO, Suhariyanto; SHOIMAH, Siti (Journal of Tourism Economics and Policy, 2023)
The original concept of internal marketing focused on providing internal products (jobs) to meet the needs of vital internal markets (employees) as well as meeting organizational needs. The marketing field still lacks knowledge on how to create and sustain internal marketing missions and goals, such as the formation of a collective mind, the alignment between employees and organizational goals, and the emergence of a positive place culture; the purpose of this study is to explore how brand community activities and internal marketing are ideally executed as a form of playing out marketing activities in expressing custom cultural reproduction. This study conducts a qualitative study of the annual routine birthday celebrations of a custom cultural community. Data was collected through in-depth interviews, supplemented by community documents and field observations. The findings of this study reveal that the success of the event is well managed to reproduce voluntary custom culture by emphasizing local wisdom norms, values and beliefs based on community event objectives. The implication for managing brand community events with the aim of building a custom community culture is more emphasis is placed on the symbolism of the sales promotion aspect of an event and providing custom community activists experience in managing a brand community event. This study shows that external marketing in managing events can create internal marketing strengths in carrying out marketing practices with local wisdom nuances.